The Effectiveness of Send-a-problem Technique to Teach Writing in the Eighth Grade of SMPN 2 Banyumas - Tri Pujiani; Ngadiso Ngadiso; Dewi Rochsantiningsih (J-LEE - Journal of Law, English, and Economics, 2019)
Send-A-Problem is one of cooperative learning techniques in which the students are involved in a discussion to solve a problem. It allows the students to practice together and learn from each other, so it is very effective to encourage the students’ self-esteem and creativity. This study aims to examine the effectiveness of Send-A-Problem technique for teaching writing of junior high school students. This experimental study was conducted at a Junior High School in Banyumas, in February 2012-March 2015. The samples of the study were taken by using cluster random sampling. The samples are two classes; those are VIIIE which was treated as experimental class taught by using Send-A-Problem and VIIIF which was treated as control class taught using by Guided Writing. Each of them consists of 30 students. The data was taken from writing test. The data was analyzed by using descriptive statistics and independent t-test. The result shows that (1) Send-A-Problem is more effective than Guided Writing for teaching writing of Junior High School. In conclusion, Send-A-Problem is an effective technique to teach writing for Junior High School students.